Modelling and experimental study of SO2 removal and NH3 recycling in an ammonia based CO2 capture process - Li, K.; Yu, H.; Feron, P.; Tade, Moses (Elsevier Ltd, 2014)
The high NH3 loss to the gas stream (NH3 slip) is one of the major issues in the ammonia based CO2 capture technology. Meanwhile, the removal of sulphur dioxide pollutant (SO2) from flue gas is a prerequisite for many CO2 capture processes. Flue gas desulphurization (FGD) is not installed in Australian power plants and significant capital/investment costs are required to install FGD. In this study, we proposed an advanced process configuration to combine SO2 removal and NH3 recycling in one process development and solve these two problems together. A rate-based model for the system of NH3-CO2-SO2-H2O was established and employed to simulate the process flow sheet. The temperature, pH and N/S ratio profile, SO2 removal and NH3 recycling efficiency along the column were analysed. Experimental work using a bubble column was carried out to provide an initial test on the technical feasibility of the SO2 and NH3 absorption process. Both the modelling and experimental results suggest that the proposed process results in excellent removal and recovery of SO2 and NH3.